2013
DOI: 10.5888/pcd10.130009
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Adult Smoking, Nebraska, 2011

Abstract: IntroductionSmoking is a public health risk; the prevalence of smoking among adults in Nebraska is 18.4%. Studies indicate that maltreatment of children alters their brain development, possibly increasing risk for tobacco use. Previous studies have documented associations between childhood maltreatment and adult health behaviors, demonstrating the influence of adverse experiences on tobacco use. We examined prevalence and associations between adverse childhood experiences and smoking among Nebraskans.MethodsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
1
14
1
1
Order By: Relevance
“…1924,31,36 However, our study extends the populations covered in previous work, with a cohort composition of Southern Blacks and Whites of similar (typically low) income and education and highlights that childhood experiences can have marked affect the underserved and vulnerable.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…1924,31,36 However, our study extends the populations covered in previous work, with a cohort composition of Southern Blacks and Whites of similar (typically low) income and education and highlights that childhood experiences can have marked affect the underserved and vulnerable.…”
Section: Discussionsupporting
confidence: 67%
“…20, 33 Individual reports have shown a four- to 12-fold increased risk of alcoholism, drug abuse, depression, and suicide attempts among people who had experienced four or more categories of adverse childhood exposures, compared with those who had experienced none, as well as increases in poorer health behaviors, including a 1.5- to four-fold increase in smoking and 1.4- to 1.6-fold increase in physical inactivity and severe obesity. 19,29,3436 …”
mentioning
confidence: 99%
“…In a study of individuals with no significant psychopathology, a 4-fold magnitude of association was found between early childhood trauma and cigarette smoking in adulthood [26]. These overall results have also been demonstrated in studies nationwide using the BRFSS data [3–6]…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have found ACEs associated with smoking in adulthood [13]. In an assessment of a large HMO clinical database, the presence of 4+ ACEs was linked to over twice the likelihood of smoking in adulthood [1].…”
Section: Discussionmentioning
confidence: 99%
“…Among youths (age 12–17 years), Hawaii ranks 2 nd in smoking prevalence [11]. The presence of ACEs is associated with greater smoking prevalence [12, 13] and may account, at least in part, for the rate of asthma and COPD in Hawaii. Other poor health factors (e.g.…”
Section: Introductionmentioning
confidence: 99%